THE CRISIS OF INTERNATIONAL LAW IN INTERNATIONAL POLITICAL ECONOMY: CASE STUDY OF SOUTH CHINA SEA DISPUTE - Obsatar Sinaga; Verdinand Robertua (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2017)
This research discussed the impact of Permanent Court of Arbitration’s decision on the dynamic of South China Sea dispute. Court’s decision in July 2016 to give South China Sea based on UNCLOS’s regulation has provoked China’s objection. This research question is on How to understand the crisis of international law in the international political economy using English School Theory in the case of South China Sea dispute? To answer the research question, this research is using English School Theory (ES) with its two pillars namely pluralism and solidarism. This research shows two findings. First, the PCA decision has been used by the Philippines to be bargaining tool to obtain economic cooperation and appeased the failure of PCA ruling. Secondly, the PCA decision has provided momentum for China to transform their policy related to the South China Sea dispute with its role as the great power. Thirdly, the structure of international law as the primary institution would be consists of great power politics, ASEAN and economic diplomacy. Key words: South China Sea, English School, Permanent Court of Arbitration, international political economy, international law Abstrak Penelitian ini membahas dampak keputusan Pengadilan Arbitrase mengenai sengketa Laut Cina Selatan. Keputusan pengadilan pada bulan Juli 2016 untuk memberi Laut Tiongkok Selatan berdasarkan peraturan UNCLOS telah memancing keberatan Tiongkok. Pertanyaan penelitian ini adalah bagaimana memahami krisis hukum internasional dalam ekonomi politik internasional dengan menggunakan Teori English School dalam kasus perselisihan Laut Tiongkok Selatan? Untuk menjawab pertanyaan penelitian, penelitian ini menggunakan Teori English School (ES) dengan dua pilarnya yaitu pluralisme dan solidarisme. Penelitian ini menunjukkan tiga temuan. Pertama, keputusan PCA telah digunakan oleh Filipina untuk menjadi alat tawar menawar untuk mendapatkan bantuan ekonomi dari China dan meredakan ketegangan akibat keputusan PCA. Kedua, keputusan PCA telah memberi momentum bagi Tiongkok untuk mengubah kebijakan mereka terkait dengan perselisihan Laut Cina Selatan dengan memainkan perannya sebagai negara adikuasa. Ketiga, struktur hukum internasional sebagai institusi primer terdiri atas politik negara adikuasa, ASEAN dan diplomasi ekonomi. Kata Kunci: Laut Tiongkok Selatan, English School, Permanent Court of Arbitration, Ekonomi Politik Internasional, hukum internasional